2020
DOI: 10.2147/cmar.s241795
|View full text |Cite
|
Sign up to set email alerts
|

<p>miR-665 Suppresses the Epithelial–Mesenchymal Transition and Progression of Gastric Cancer by Targeting <em>CRIM1</em></p>

Abstract: Background: Gastric cancer (GC) is one of the most common aggressive cancers and is characterized by high mortality. Increasing evidence has shown that microRNA-665 (miRNA-665) serves as inhibiting-miRNA in cancers. However, the role of miR-665 in GC is yet unclear. Methods: miR-665 was first analyzed using bioinformatics. Subsequent quantitative realtime PCR was used to detect miR-665 expression levels in different GC cell lines and tissues. The function of miR-665 in GC cells was determined via Cell Counting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 33 publications
5
18
0
Order By: Relevance
“…MiRNA expression profile is related to the characteristics of diverse cancers and can be used for screening differentially expressed miRNAs [22,23]. Through microarray analysis, we found that the expression of miR-4636, miR-1298, miR-4268, miR-4290, miR-1275, miR-148a-3p, miR-375, miR-943 and miR-665 were downregulated in GC tissues, which is consistent with the previous research findings [9,[24][25][26][27][28][29][30][31]. Herein, we mainly focused on miR-1269b.…”
Section: Discussionsupporting
confidence: 89%
“…MiRNA expression profile is related to the characteristics of diverse cancers and can be used for screening differentially expressed miRNAs [22,23]. Through microarray analysis, we found that the expression of miR-4636, miR-1298, miR-4268, miR-4290, miR-1275, miR-148a-3p, miR-375, miR-943 and miR-665 were downregulated in GC tissues, which is consistent with the previous research findings [9,[24][25][26][27][28][29][30][31]. Herein, we mainly focused on miR-1269b.…”
Section: Discussionsupporting
confidence: 89%
“…In osteosarcoma, miR-665 regulates Rab23 expression to inhibit tumor invasion and metastasis ( 35 ). Additionally, miR-665 suppresses epithelial–mesenchymal transition (EMT) and gastric cancer progression by targeting cysteine-rich motor neuron protein 1 (CRIM1) ( 36 ). However, little is known about the function of miR-665 in EC as well as the association between lncRNA DCST1-AS1 with miR-665.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing research efforts have been engaged to elucidate the anti-tumour roles of miR-665 in human cancer (38)(39)(40). For example, miR-665 downregulation was reported to reverse the suppressive effects of the lncRNA RHPN1-AS1 on the proliferation and migratory and invasive abilities of OC cells (38).…”
Section: Discussionmentioning
confidence: 99%